Integrasi Sistem ESP32 dengan Pemantauan Cuaca Menggunakan Sensor Meteorologi - Prayoga, Yusma'el Khammi; Arfianto, Afif Zuhri; Riananda, Dimas Pristovani; Muhammad Khoirul Hasin; Adianto; Ryan Yudha Adhitya (Indonesian Society of Applied Science (ISAS), 2025)
This study proposes an ESP32-based system integration for real-time weather monitoring using meteorological sensors including wind speed, wind direction, and rainfall sensors. ESP32 is chosen as the main platform because of its capability in wireless communication (Wi-Fi and Bluetooth) and its efficiency in processing sensor data with low power consumption. This system combines meteorological sensors to measure wind speed, wind direction, and rainfall, which are then displayed directly on the Nextion screen. The collected data will be updated in real-time, providing easily accessible information. The purpose of this study is to develop an effective and integrated weather monitoring system. The test results show that this system can collect and display data accurately on Nextion, providing an efficient and practical weather monitoring solution.